Disparity in Bankruptcy Rulings: Rethinking the Principle of Simple Proof in the Indonesian Commercial Judiciary - Abrielmovich, Biyandra Timothee; Joesoef, Iwan Erar (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study investigates the principle of simple proof in Indonesian bankruptcy law, as stipulated in Article 8(4) of Law No. 37 of 2004, and its inconsistent application in judicial practice. The purpose of the research is to critically examine the disparity in court decisions regarding the interpretation of "simple proof" and to propose a more objective and balanced evidentiary standard. Employing a normative juridical methodology, the study integrates statutory, case-based, and conceptual approaches, focusing on the Central Jakarta Commercial Court Decision No. 23/Pdt.Sus-Pailit/2022 and its affirmation by the Supreme Court Decision No. 1714 K/Pdt.Sus-Pailit/2022. These rulings illustrate a substantive judicial interpretation that deviates from the formal criteria of simple proof, resulting in the dismissal of a bankruptcy petition despite the fulfillment of normative requirements. The findings reveal that the absence of clear parameters for simple proof has led to disparities in judicial decisions, undermining legal certainty and creditor protection. The originality of this study lies in its typological classification of disparity in Indonesian bankruptcy rulings and its formulation of a proposed evidentiary framework aimed at reducing judicial inconsistency. The research recommends issuing a Supreme Court Circular (SEMA) or revising the Bankruptcy Law to ensure consistent, equitable adjudication. These reforms are essential to upholding the principles of justice and balance in bankruptcy proceedings.